2012
DOI: 10.2466/25.23.pms.115.6.895-902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Different Training Programs with Same Workload on Throwing Velocity by Experienced Water Polo Players

Abstract: To investigate the effects of two different strength-training programs with the same workload (impulse) on throwing velocity in water polo, 30 water polo players (M age = 17.1 yr., SD = 4.9; M mass = 71.2 kg, SD = 14.7; M height = 1.75 m, SD = 0.09 m) were randomly divided in two groups based upon throwing performance with water polo ball. The medicine-ball training group performed 3 x 6 reps with a 3-kg medicine ball, while the combination training group completed 1 x 9 repetitions with the 3-kg medicine ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…With regards to plyometric training for the upper body, Marques et al compared the effects of a training program using throwing exercises conducted in the stretch shortening cycle [ 78 ]. While one experimental group exercised with heavy balls (3 kg), the other group exercised with a combination of heavy balls and water polo balls (approximately 0.4 kg).…”
Section: Resultsmentioning
confidence: 99%
“…With regards to plyometric training for the upper body, Marques et al compared the effects of a training program using throwing exercises conducted in the stretch shortening cycle [ 78 ]. While one experimental group exercised with heavy balls (3 kg), the other group exercised with a combination of heavy balls and water polo balls (approximately 0.4 kg).…”
Section: Resultsmentioning
confidence: 99%
“…Throwing is one of the most decisive technical actions in many team sports and has been studied in various sports modalities including water polo (Marques et al, 2012), cricket (Van den Tillaar & Marques, 2011) and baseball (Newton & McEvoy, 1994;Lachowetz, Evon & Pastiglione,1998). Studies have shown that the speed of throwing influences the reaction time of the opponent for intercepting the ball (Van den Tillaar & Ettema, 2003, Gutierrez-Davila, Rojas, Ortega, Campos & Párraga, 2011) and throwing at the fastest possible speed is a factor that determines sporting success in attack situations (Vila et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gorostiaga, Granados, Ibáñez and Izquierdo, (2005) and Ortega-Becerra, Pareja-Blanco, Jiménez-Reyes, Cuadrado-Peñafiel and Gonzalez-Badillo (2018) indicate that throwing mechanics, strength and muscular power in the upper and lower body segments are factors that increase speed rates in specific handball throws. To improve throw velocity, different training programs have been carried out focused on both strength and velocity (Potteiger, Williford, Blessing & Smidt, 1992) based on the principle of overloading of the upper body segments (Gorostiaga, Izquierdo, Itralde, Ruasta & Ibáñez, 1999;Marques et al, 2012), and on the principle of specificity with regard to throws in this sport (Lachowetz et al, 1998;van der Tillaar & Ettema, 2003, 2011van der Tillar, 2004;van der Tillar & Marques, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have highlighted that of all the actions that impact water polo performance, throws are one of the most decisive technical skills in terms of the outcome of a match (Marques, et al, 2012 However, very little of this research was carried out based on throws which took place in official Championships in real game situations (Abraldes, et al, 2011;Alcaraz, et al, 2011;Alcaraz, et al, 2012), where there are other factors that can have an impact (there are differences between throw speed in training and/or competition), as well as the presence of opponents, the micro-situation in which the throw is performed (even, counterattack, power play and penalty), the angle or position of the throw and the distance from the goal at which the throw was made.…”
Section: Introductionmentioning
confidence: 99%